2008
DOI: 10.1088/1367-2630/10/10/103025
|View full text |Cite
|
Sign up to set email alerts
|

Closed timelike geodesics in a gas of cosmic strings

Abstract: We find a class of solutions of Einstein's field equations representing spacetime outside a spinning cosmic string surrounded by vacuum energy and a rotating gas of non-spinning strings of limited radial extension. Outside the region with vacuum energy and cosmic strings there is empty space. We show that there exist closed timelike geodesics in this spacetime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
0
20
0
4
Order By: Relevance
“…Since the conditions (36) and (37) manifestly hold if (38) does, we conclude that there is a significant range in the parameter space (x 0 , y ) in which our wormhole model completely satisfies the WEC.…”
Section: Potentially Observable Modelsmentioning
confidence: 77%
See 1 more Smart Citation
“…Since the conditions (36) and (37) manifestly hold if (38) does, we conclude that there is a significant range in the parameter space (x 0 , y ) in which our wormhole model completely satisfies the WEC.…”
Section: Potentially Observable Modelsmentioning
confidence: 77%
“…A question of interest is whether the space-time described by this solution contains closed timelike curves (CTCs) that lead to causality violation. In the metric (1) such curves emerge if and only if g 33 > 0 (see, e.g., [37]), in which case the closed coordinate lines of the azimuthal angle ϕ are timelike. Consider the behavior of g 33 for the symmetric branch of the above solution, to be used in what follows.…”
Section: Wormhole Solution With An Anisotropic Fluidmentioning
confidence: 99%
“…Bonnor and Steadman [25] have shown that a spacetime with two spinning particles, under special circumstances, allow for the existence of CTGs. A class of solutions of Einstein's field equations with CTGs representing spacetime outside a spinning cosmic string surrounded by a region of finite radial extension with vacuum energy and a gas of strings [26] have been recently found. Other examples are a cylindrically symmetric spacetime [27] which admit CTGs everywhere outside an axis and a vacuum spacetime with CNGs found quite recently [28].…”
Section: Introductionmentioning
confidence: 99%
“…Thus when r 0 > 6 m, the constant ω is real and the solution (14) shows the typical behavior for stability, i.e., vibrational modes untangled with translational ones that can be eliminated by a suitable choice of the initial conditions.…”
mentioning
confidence: 99%